ALLES SO SCHÖN SCHWUL* HIER...? - Oliver, Klaassen (Institut für Materielle Kultur, 2015)
Since 2008 the Gay Museum* (= Schwules Museum*) in Berlin has been reassessing its exhibition and collection practice by exploring what is means to be queer. In other words, the question is how highly complex debates and divergent recognition strategies within the LGBT*I/Q movement can be done differently and in a more democratic way within the museum. A central part of my bachelor thesis is a discussion of critical and emancipatory potential of queer‐feminist imagery and art politics for the exhibition practices of the Gay Museum*. With the thesis presented here, I address and attempt to answer the following question: How can the Gay Museum* become an accepted platform that provokes and negotiates the normalization of hetero‐ and homo‐centric and sexuality discourse? After an exposition of central theoretical concepts, with a particular reference to the methodology of queer‐feminist critique of representation, I give a brief overview of the genesis, meaning and foundation history of the Gay Museum*. I then examine the intentions and outcomes of the exhibition “trans*_homo – of lesbian trans*gays and other normalities” (17.08.‐19.11.2012) through a critical perspective. Specifically, I analyze how and whether in this exhibition action was taken at the level of representation in natural attributions of sexuality and gender. Following my critical analyzes, I explore both potentials as well as the boundaries of queer‐feminist impulses. Ultimately, I want to embed my preliminary findings from the analysis into a theoretical context for discussion. Above all, I intend to contribute to the academic conversation and examination about whether or not the function of the Gay Museum* as a discursive venue of LGBT*I/Q actually can change our modern apparatus. My primarily goal is to present a programmatic image of queer‐feminist politics of representation for exhibition practices and in so, to the extensive field of sexual and gender identity construction, which still holds many unresolved questions and contradictions. As I hope to show, exhibitions have the capacity to do intensive and varied work on the deconstruction and rearrangement of the hegemonic museum practice. The analyzed exhibition therefore provides important consideration for the future practical work and theory of the Gay Museum* as a discursive venue of identity politics (gender and sexuality).
Überlegungen zu repräsentationskritischen Potenzialen, Bedingungen und Perspektive für die inhaltliche Neuausrichtung des Schwulen Museums* in Berlin für die inhaltliche Neuausrichtung des Schwulen Museums* in Berlin
Keywords: Queer Theory; Repräsentation; Kritik; Kunst; 700 Künste, Bildende und angewandte Kunst; Museum